1999
DOI: 10.1002/(sici)1096-8644(199907)109:3<303::aid-ajpa3>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Hyperostosis frontalis interna: An anthropological perspective

Abstract: Hyperostosis frontalis interna (HFI) is manifested by the accretion of bone on the inner table of the frontal bone. Despite the vast literature on HFI, ambiguity exists as to its etiology, osteogenesis, demography, and history. This stimulated the present broad-scale study of HFI which included the evaluation of 1,706 early 20th century skulls (1,007 males and 699 females) from the Hamann-Todd and Terry human osteological collections, as well as 2,019 pre-19th century East-Mediterranean, Amerindian, and Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
178
0
49

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(232 citation statements)
references
References 19 publications
5
178
0
49
Order By: Relevance
“…However, Hershkovitz et al (1999) determined that HFI is an independent phenomenon, and other research ers have found that HFI can be asymptomatic (Jaffe 1972;Salmi et al 1962). Although alter ations in cranial vascularization and nerve function cannot be dismissed as possible con tributing factors (Hershkovitz et al 1999), the general consensus is that HFI is related to an imbalance or disturbance in the endocrine sys tem. Hershkovitz et al (1999) postulate that the condition arises from prolonged estrogen stimu lus, thus explaining its greater presence in females and greater severity in older females.…”
Section: Miscellaneous Skeletal Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Hershkovitz et al (1999) determined that HFI is an independent phenomenon, and other research ers have found that HFI can be asymptomatic (Jaffe 1972;Salmi et al 1962). Although alter ations in cranial vascularization and nerve function cannot be dismissed as possible con tributing factors (Hershkovitz et al 1999), the general consensus is that HFI is related to an imbalance or disturbance in the endocrine sys tem. Hershkovitz et al (1999) postulate that the condition arises from prolonged estrogen stimu lus, thus explaining its greater presence in females and greater severity in older females.…”
Section: Miscellaneous Skeletal Disordersmentioning
confidence: 99%
“…This manifestation is consistent for hyperosto sis frontalis interna (HFI), a condition that appears to be present more often in women than men and with stronger expression among females. It also appears to occur most often in individu als over the age of 40 (Hershkovitz et al 1999). Despite much discussion in the anthropologi cal and medical literature (e.g., Armelagos and Chrisman 1988;Hawkins and Martin 1965;Hershkovitz et al 1999;Jaffe 1972;Salmi et al 1962), the specific etiology and effects of the dis order remain to be determined.…”
Section: Miscellaneous Skeletal Disordersmentioning
confidence: 99%
See 3 more Smart Citations